IMPLEMENTASI KURIKULUM PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI (SMP) SATAP 3 BAYAN - Maulana Akbar; Sri Endang Erningsih (Prodi PAI STIT Sunan Giri Bima, 2023)
The curriculum is an important component in the implementation of education. The implementation of the curriculum in educational units are expected to be able to achieve national education goals. Islamic religious education is a means of increasing Islamic values through the school education process. For this reason, it is necessary to study the application the curriculum of Islamic religious education starting from the planning, processes and obstacles encountered in the field. The method used in this study is a qualitative method with data collection in the form of interviews and observations. The implementation curriculum of Islamic religious education at SMPN Satan 3 Bayan is quite good. This statement can be seen from the learning tools made by teacher such as the learning implementation plan that is implemented properly and according to the provisions of the basic listed in the curriculum.